Analisis Kepuasan Orang Tua Siswa Dalam Layanan Pendidikan di Madrasah Ibtidaiyah Nurul Huda Kota Dumai - Syawal Simatupang (LPPI Yayasan Almahmudi bin Dahlan, 2025)
This study aims to analyze the level of parental satisfaction with educational services at Madrasah Ibtidaiyah (MI) Nurul Huda Dumai City. The research employed a descriptive method with both quantitative and qualitative approaches. Data were collected through questionnaires distributed to 46 parents as samples using a random sampling technique. The research instrument was developed based on service quality dimensions (SERVQUAL), specifically focusing on three main dimensions: reliability, assurance, and tangibles. The results of the data analysis indicated that the parental satisfaction level reached 75%, which falls into the